Teacher Quality and Learning Outcomes in Kindergarten - María Caridad Araujo; Pedro M. Carneiro; Yyannú Cruz Aguayo; Norbert Rüdiger Schady (Inter-American Development Bank (IDB), 2016)
We assigned two cohorts of kindergarten students, totaling more than 24,000 children, to teachers within schools with a rule that is as-good-as-random. We collected data on children at the beginning of the school year, and applied 12 tests of math, language and executive function (EF) at the end of the year. All teachers were filmed teaching for a full day, and the videos were coded using a well-known classroom observation tool, the Classroom Assessment Scoring System (or CLASS). We find substantial classroom effects: A one-standard deviation increase in classroom quality results in 0.11, 0.11, and 0.07 standard deviation higher test scores in language, math, and EF, respectively. Teacher behaviors, as measured by the CLASS, are associated with higher test scores. Parents recognize better teachers, but do not change their behaviors appreciably to take account of differences in teacher quality.
hdl:11319/7425
Keywords: I24; I25; 330; Teacher quality; learning; test scores